2007
DOI: 10.1093/rpd/ncm268
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal absorbed fractions for electrons in the adult male: considerations of a revised 50- m definition of the bone endosteum

Abstract: In 1995, the International Commission on Radiological Protection (ICRP) issued ICRP Publication 70 which provided an extensive update to the physiological and anatomical reference data for the skeleton of adults and children originally issued in ICRP Publication 23. Although ICRP Publication 70 has been a valuable document in the development of reference voxel computational phantoms, additional guidance is needed for dose assessment in the skeletal tissues beyond that given in ICRP Publication 30. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…The MASH2 bone endosteum mass is almost 16% smaller than the reference value given in ICRP110. ICRP110 refers to a paper of Bolch et al (2007), but unfortunately the authors did not provide enough information which could help to explain the disagreement. However, good agreement was found with data published by Watchman et al (2007), who used a completely different method for the calculation of skeletal tissue masses.…”
Section: Segmentation Of Skeletal Tissuesmentioning
confidence: 99%
“…The MASH2 bone endosteum mass is almost 16% smaller than the reference value given in ICRP110. ICRP110 refers to a paper of Bolch et al (2007), but unfortunately the authors did not provide enough information which could help to explain the disagreement. However, good agreement was found with data published by Watchman et al (2007), who used a completely different method for the calculation of skeletal tissue masses.…”
Section: Segmentation Of Skeletal Tissuesmentioning
confidence: 99%
“…12 However, it has recently been suggested that in addition to cortical bone surfaces adjacent to spongiosa, medullary cortical bone surfaces of arm and leg bones should also be taken into account when determining the equivalent dose to the BSC. 19 Medullary cortical bone surfaces form the walls of large, tubelike cavities in the upper and lower arm and leg bones, also called "long bones," filled for adults only with yellow bone marrow ͑YBM͒, which is not considered to be a target tissue for skeletal dosimetry.…”
Section: Iic Medullary Cortical Bone Surfacesmentioning
confidence: 99%
“…BSC can also be found on the surfaces of cortical bone, but "because cell proliferation is greater on trabecular than on cortical surfaces, it is to be expected that malignant transformation will occur more readily in the endosteum of trabecular bone" (Spiers 1974). Discussion about the location and the distribution of the two skeletal tissues at risk is still ongoing with respect to the revision of the thickness of the BSC layer from 10 to 50 m, the exclusion of the Haversian canals of cortical bone, the inclusion of cortical surfaces of the medullary cavities (Bolch et al 2007), the consideration of trabecular bone remodelling (Richardson et al 2007) and the inhomogeneous distribution of RBM cells in the marrow (Watchman et al 2007a).…”
Section: The Skeletal Tissues At Riskmentioning
confidence: 99%